Analisis Mendalam Puisi "Karawang-Bekasi" oleh Chairil Anwar - Ezra Natasya Hutabarat; Najla Haifa Maulidina Tarigan; Rosmawaty Harahap (Jurnal Kewarganegaraan, 2024)
Abstract Many people know about the poem 'Karawan Bekasi' by Cairil Anwar, but only a few know the events behind the creation of Cairil Anwar's legendary poem. If we can understand and interpret the meaning of the poem Karawang Bekasi by Charil Anwar, then we can understand the situation of the Karawang Bekasi Front during the Physical Revolution to Defend Independence (1945-1949) and the fighters at that time made such choices. The Karawang-Bekasi Front fought against NICA (Netherlands Indian Civil Administration). The poems created by Cairil Anwar are the inner experiences felt by Cairil Anwar based on the situation and conditions at that time, thus allowing him to express his imagination and thoughts, and the legendary Karawang Bekasi poems were created with the theme of patriotic nationalism. Keywords: Karawang Bekasi, Chairil Anwar, Independence, Fighter, Experience Abstrak Banyak orang yang mengetahui tentang puisi 'Karawang Bekasi' karya Cairil Anwar, namun hanya sedikit yang mengetahui peristiwa di balik penciptaan puisi legendaris Cairil Anwar tersebut. Makna puisi Karawang Bekasi karya Charil Anwar, situasi Front Karawang Bekasi pada masa Revolusi Fisik Mempertahankan Kemerdekaan (1945-1949) dan para pejuang pada saat itu membuat pilihan seperti itu. Front Karawang-Bekasi berperang melawan NICA (Netherlands Indian Civil Administration). Puisi-puisi yang diciptakan oleh Cairil Anwar merupakan pengalaman batin yang dirasakan Cairil Anwar berdasarkan situasi dan kondisi saat itu, sehingga memungkinkan ia mengekspresikan imajinasi dan pemikirannya, dan puisi-puisi legendaris Karawang Bekasi diciptakan dengan tema patriotik nasionalisme. Kata Kunci: Karawang Bekasi, Chairil Anwar, Kemerdekaan, Pejuang, Pengalaman